QUALITY IMPROVEMENT IN THE PRODUCTION OF AUTOMOTIVE CASTING PARTS USING SIX SIGMA APPROACH - Rinawati, Dyah Ika (J@ti Undip: Jurnal Teknik Industri, 2024)
The implementation of Six Sigma methodology has proven to be highly effective in enhancing quality and reducing defects in manufacturing processes. This paper investigates the application of Six Sigma principles to reduce defects in the production of automotive casting parts, specifically cylinder block. By utilizing the Define, Measure, Analyze, Improve, and Control (DMAIC) framework, the study identifies critical factors contributing to defects and implements strategic improvements to mitigate these issues. It showed that the "Sunakui" was the most common type of defects in the casting process.  In measure phase, the defect per million opportunity of product was measured by the value of 5,064 with the sigma value of 4,091σ. Our study determined that the main factor leading to faults was the presence of wrong or unsuitable sand composition. To address this issue, we recommend implementing a Poka-Yoke system with an alarm to monitor and ensure the appropriate sand composition. The result suggested significant reductions in defect rates, leading to improved product quality.